Cooperative target tracking in vehicular sensor networks - Ramos, Heitor S.; Boukerche, Azzedine; Pazzi, Richard W.; Frery, Alejandro C.; Loureiro, Antonio A.F. (IEEE wireless communications, 2012)
Target tracking plays a key role for vehicular ad hoc networks (VANETs) due to the fact that a wide variety of envisioned applications rely on the ability of this technique of detecting, localizing, and tracking objects surrounding a vehicle. This subject has been studied in fields such as airborne traffic, computer vision, and wireless sensor networks. A VANET brings out new challenges that should be addressed. For instance, the cluttered and dense scenarios, communication issues such as short term links, and the variety of objects considered to be targets, are some of the new ingredients to be taken into account. Applications such as collision warning/avoidance systems require strict time constrains, while others impose only mild restrictions. This complex and heterogeneous environment is discussed in this work, where we didactically divide the main problems into four components: the targets' motion model, measurement models, data association problem, and filtering. We also discuss the communication issues and how they affect these systems.